Producing Neurospheroids and Hydrogels to Create a Three-dimensional in Vitro Model for the Use of Conduits in Peripheral Nerve Regeneration. Issue 5 (23rd March 2019) - Shete, Devyani; Batth, Aran; Nijhawan, Aditi; Choudhary, Jaffer; Thompson, Ian
Abstract: INTRODUCTION: Peripheral nerve regeneration is a complex challenge that requires suitable nerve guidance systems to bridge the severed ends of 2 nerves back together. Current polymeric conduits on the market provide good cellular growth but are limited by the length of gap defect they can repair, and complete functional recovery is rare. This project focused on creating a three-dimensional (3D) in Vitro spheroidal sprouting assay for peripheral nerve regeneration, as well as producing and testing different polymeric hydrogels as potential scaffold materials for the conduit. METHODS: Different concentrations of chitosan, methylcellulose (MC) and sodium alginate were produced, as well as blends of these materials. These hydrogels were seeded with 3D neurospheroids, along with NG108-15 (neuronal) cells and Schwann cells to test their biocompatibility. RESULTS: MTT assays showed the mean absorbance of chitosan gels with NG108-15 cells at 24 hr ( P  < .001) and 72 hr ( P  > .05) was similar/slightly higher than the negative control. Live-Dead data showed 93.4% of live cells at DIV7 on MC: Ch blends, compared to 72% with chitosan alone. CONCLUSION: Overall, both chitosan and MC were nontoxic and biocompatible with NG108-15 and Schwann cells. Blending chitosan with MC improved its chemical and physical properties. The cells formed spheroids that well on a gel; this pseudo-3D structure is excellent for research purposes compared to 2D as it mimics the body's internal environment.